PELATIHAN PEMBUATAN KOMBUCHA TEH KAYU ARO SEBAGAI MINUMAN PROBIOTIK PADA IBU-IBU PKK DESA PAUH MENANG - Widia Putri Febriani; Rizki Apriadi Bahri; Rica Sofiana Sari; Leni Marlina; Gepri; Naimah; Resi Juanda (AbdiMasya | Hira Institute, 2024)
Kayu Aro is one of the sub-districts in Kerinci Regency, Jambi Province, which is known to have a mountainous area with suburban land that is very suitable for tea cultivation. Most of the tea produced is still sold in the form of standard black tea or green tea. In fact, there is great potential to develop more diverse processed tea products, such as kombucha. Kombucha is a probiotic drink that can boost the immune system and help fight various diseases caused by microorganisms. This activity aims to introduce the benefits of kombucha to PKK women in Pauh Menang Village as an alternative healthy drink that they can consume every day for a healthy diet and a better lifestyle and be used as a profitable business opportunity and provide opportunities for PKK women to learn to utilize local raw materials available around them. The methods used are Observation, Counseling, Direct Practice and Evaluation. Based on the results of the post-test, this community service activity succeeded in attracting the interest of PKK women and increasing the understanding and skills of PKK women in Pauh Menang Village regarding kombucha and becoming facilitators for the community in promoting healthy living.